Unbiased FIR, Kalman, and game theory H∞ filtering under bernoulli distributed random delays and packet dropouts - Uribe-Murcia, Karen; Shmaliy, Yuriy S.; Andrade-Lucio, José A. (Neurocomputing (Amsterdam), 2021)
It is known that due to uncertain delays and missing data wireless sensor networks (WSNs) may incur a significant loss in performance. In this work, we solve the problem in discrete-time state-space by developing the unbiased finite impulse response (UFIR) filter, Kalman filter (KF), and game theory H∞ filter for systems with randomly delayed data and packet dropouts. The binary Bernoulli distribution is adopted for WSN channels to model the arrival data with supposedly known delay-time probability. The effectiveness of the UFIR filter, KF, and H∞ filter is compared experimentally in terms of accuracy and robustness employing the GPS-measured vehicle coordinates transmitted with latency over WSN.